The millipede family Striariidae Bollman, 1893. VI. Six new genera and thirteen new species from western North America (Diplopoda, Chordeumatida, Striarioidea) - Shear, William A.; Marek, Paul E. (Zootaxa, 2022)
The following new genera and species of Striariidae are described from the states of California, Oregon and Washington: Nototrisaria ornata n. gen., n. sp., Maraplia napa n. gen., n. sp., Maraplia chico n. gen., n. sp., Maraplia schusteri n. gen., n. sp., Lamparia curryensis n. gen., n. sp., Lamparia bentonensis n. gen., n. sp., Lamparia pratensis n. gen., n. sp., Lamparia millicoma n. gen., n. sp., Rampalia cheathamensis n. gen., n. sp., Plaramia arcata n. gen., n. sp., Plaramia johnsonae n. gen., n. sp., Ralampia complexa n. gen., n. sp., and Ralampia filamentosa n. gen., n. sp.. The new species are all very small millipedes, 5.5 mm or less in length and with two or three ommatidia on each side of the head or blind. The majority have the sixth metazonital crest larger than the other crests and extended horizontally, so that the animals have the general appearance of having paranota. A new key to striariid genera is presented.